If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + 9k = 62 Solving -10 + 9k = 62 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 9k = 62 + 10 Combine like terms: -10 + 10 = 0 0 + 9k = 62 + 10 9k = 62 + 10 Combine like terms: 62 + 10 = 72 9k = 72 Divide each side by '9'. k = 8 Simplifying k = 8
| 5x^2-14x-76=0 | | x-.10x=150 | | 7(8x+8)=56x-1 | | 13-50=20(5x-9x)+6x | | -1-(-12)= | | 8t/6 | | 2*15/7 | | cbrt(2x-3)=3 | | 11-12x=-11s | | 4(-3x)+y=2 | | 0.166666667x=4 | | 15y+9x=30 | | 8y+7=9y-1 | | 52=4(s-67) | | 5-5cosx=0 | | 9*b+4=7 | | -26-49= | | -8(-3-2n)=104 | | -7+2(1-5s)=35 | | 9*-b+4=7 | | p/3=1/8 | | 13y-7y=18 | | 81/9*(10-1)=x | | (10i)/(6-5i) | | k^2+10k-65=-9 | | 10y+32=92 | | 8-9=39 | | 3x^2+18x-43=5 | | Y-2=-1/5(x-5) | | -4-(-5)/7=13 | | -9(z-97)=45 | | 8=7z-(3-9z)-2z |